Nordic Walking Training Causes a Decrease in Blood Cholesterol in Elderly Women Supplemented with Vitamin D - Prusik, Krzysztof; Kortas, Jakub; Prusik, Katarzyna; Mieszkowski, Jan; Jaworska, Joanna; Skrobot, Wojciech; Lipinski, Marcin; Ziemann, Ewa; Antosiewicz, Jedrzej (Frontiers in Endocrinology, 2018)
Objective Different studies have demonstrated that regular exercise can induce changes in the lipid profile, but results remain inconclusive. Available data suggest that correction of vitamin D deficiency can improve the lipid profile. In this study, we have hypothesized that Nordic Walking training will improve lipid profile in elderly women supplemented with vitamin D. Methods A total of 109 elderly women (68 ± 5.12 years old) took part in the study. First group [experimental group (EG): 35 women] underwent 12 weeks of Nordic Walking (NW) training combined with vitamin D supplementation (4,000 IU/day), second group [supplementation group (SG): 48 women] was only supplemented with vitamin D (4,000 IU/day), and third group [control group (CG): 31 women] was not subject to any interventions. Blood analysis of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and 25-OH-D3 was performed at baseline and after the 12 weeks of NW training. Additionally, a battery of field tests specifically developed for older adults was used to assess the components of functional fitness. The same blood analysis was repeated for the EG 6 months after the main experiment. Results After 12 weeks of NW training and vitamin D supplementation, in the EG a decrease in TC, LDL-C, and TG was observed. In the SG, no changes in the lipid profile were observed, whereas in the CG an increase in the HDL-C level was noticed. Positive physical fitness changes were only observed in the EG. Conclusion Our obtained data confirmed baseline assumption that regular exercise induces positive alternations in lipid profile in elderly women supported by supplementation of vitamin D.